(3efJNH ef GdKdK GdKGfj ef GdWHbGJ GdcHQi ddSHcj JGL GdOjf YHOGdhgGH Hf Ydj GdeJhaj SfI (B771 (3g`s - (3eLghds; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s
(3ChdgG (B:s
(3GdWHbI GdQGHYI ajef Jhai Hjf GdCQHYeGFI hGdNeSeGFI s
(3BNQgG (B:s
(3BNQg eHJhQ hBNQ eGajg aEfg fbd HYO ehJg HGKfJi YTQI SfI Edi LHd bGSjhf , hOaf HGdRGhjI GdeYQhaI Hge , hbO RQJ bHQg eQGQkG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B104 - (3U(B247s
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B432 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs